2012
DOI: 10.1186/1756-0500-5-434
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability and construct validity of the ENERGY-parent questionnaire on parenting practices, energy balance-related behaviours and their potential behavioural determinants: the ENERGY-project

Abstract: BackgroundInsight in parental energy balance-related behaviours, their determinants and parenting practices are important to inform childhood obesity prevention. Therefore, reliable and valid tools to measure these variables in large-scale population research are needed. The objective of the current study was to examine the test-retest reliability and construct validity of the parent questionnaire used in the ENERGY-project, assessing parental energy balance-related behaviours, their determinants, and parentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 9 publications
4
64
2
Order By: Relevance
“…For the item 'In general, how often do you watch television during breakfast? ', ICC was 0?74 with 83 % agreement (38) .…”
Section: Parent Questionnairementioning
confidence: 93%
See 2 more Smart Citations
“…For the item 'In general, how often do you watch television during breakfast? ', ICC was 0?74 with 83 % agreement (38) .…”
Section: Parent Questionnairementioning
confidence: 93%
“…Based on the 'skipping breakfast' variable and the 'TV during breakfast' variable, a new variable coded 1-3 was created: breakfast skippers (coded 1), breakfast with TV (coded 2; containing only those reporting to eat breakfast every day) and breakfast without TV (coded 3; containing only those eating breakfast every day). Test-retest reliability of the items measuring these selected behaviours appeared to be good to excellent for the total study sample, in a separate test-retest and construct validity study, as expressed by the intra-class correlation coefficient (ICC) and percentage agreement (38) . For the question 'From Monday to Friday, how many days do you usually eat breakfast?…”
Section: Parent Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…To code the binary variable of parent's PA the guidelines for adults (30 min of PA per day) were used. The test-retest reliability and construct validity of the children's questionnaire and parental questionnaire (Singh et al, 2012) are reported elsewhere. From the children's questionnaire 80% of PA's items showed good to excellent test-retest reliability as indicated by intra-class correlation coefficients (ICCs) >0.60.…”
Section: Physical Activitymentioning
confidence: 99%
“…The data collection protocol and survey questionnaires used for the ENERGY cross-sectional survey are available online (http://projectenergy.eu). Detailed information regarding the development, validity and reliability of the child questionnaire is published elsewhere (17,20,21) .…”
Section: Data Collectionmentioning
confidence: 99%